Mnemosine, Clio e a memória histórica da educação de jovens e adultos em/com ações de extensão na UFES de 1986 a 1996 - Vieira, Tatiana de Santana (2017)
The research investigates the history of the education of young people and adults (EJA) in three extension projects of the Federal University of Espírito Santo (UFES), developed between 1986 and 1996, that encompassed the process of democratization post Civilian/Military Dictatorship till the creation of the Law of Guidelines and Bases for the Education, Law no. 9.394/96 and the institutionalization of the Education for Young people and Adults Nucleus (NEJA) at UFES. In the light of the overall objective which is to make visible the historical memories of the EJA by means of sources generated in the practices and formation processes of the extension actions, the research develops the methodology of a qualitative nature and historical perspective. It adopts documents-monuments, narratives of subject, written and imagistic sources as memory trends for the interpretation of the remains that (re)build part of the history of the EJA. It highlights the constitution of the NEJA as a place of memory, bringing in itself as a strong mark of resistance and political action in favor of development of educator’s formation, literacy and post-literacy for youth and adults. It also brings to light the prevailing methodological and theoretical developed by NEJA. The memories of the projects denote that to the extension that EJA was reconfigured by the public educational policies, the principles of popular education have lost ground. The results indicate the prevalence of silencing about the EJA memories, especially in the estate of Espirito Santo. In this way, the memories of the NEJA collaborate with the reconstruction of a history marked by the strength and persistence to assert education as a right for young people and adults.